Odpowiedź :
Odpowiedź:
2x-3x=8
3x-3=8
3x=8+3
3x=11
x=11/3
3x-2x+3=1
x+3=1
x=1-3
x=-2
4x+x/3=4
12x+x=12
13x=12
x=12/13
8-2x/2=10
16-2x=20
-2x=20-16
-2x=4
x=4/-2
x=-2
3/4x-5+1/4x=10
x-5=10
x=10+5
x=15
Odpowiedź:
a) 2x - 3+x=8
3x - 3=8
3x=8 +3
3x=11/:3
x=11/3=3 2/3
b) 3*5x - 7=3
15x - 7=3
15x=3+7
15x=10/:15
x=10/15=2/3
c)3x - 2x+3=1
x+3=1
x=1 - 3
x= - 2
d) 4x+x/3=4
13/3x=4 /*3/13
x=12/13
e) 8 - 2x/2=10
8 - x=10
- x=10 - 8
- x=2/:( - 1)
x= - 2
f) 3/4x - 5+1/4x=10
x - 5=10
x=10+5
x=15
Szczegółowe wyjaśnienie: